Charakterystyka i funkcje struktur holdingowych tworzonych na bazie przedsiębiorstw państwowych - Lubomska-Kalisz, Jolanta (Characteristics and functions of holding structures created on the base of state enterprises, 2006)
Holding structures have often been created within a period of the transformation of the Polish economy on the base of state enterprises. They turned out useful in restructuring of Polish companies. Synthetic characteristics of holding structures and their function were restated in the article. The estimation of the mark of the realization of the function was carried out on the basis of empirical examinations through Polish holdings.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 466-471